2019
DOI: 10.1371/journal.pntd.0007334
|View full text |Cite
|
Sign up to set email alerts
|

Arboviral screening of invasive Aedes species in northeastern Turkey: West Nile virus circulation and detection of insect-only viruses

Abstract: Background The recent reports of Aedes aegypti and Ae . albopictus populations in Turkey, in parallel with the territorial expansion identified in several surrounding countries, have raised concerns about the establishment and re-establishment of these invasive Aedes mosquitoes in Turkey. This cross-sectional study was performed to detect Aedes aegypti and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
20
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(22 citation statements)
references
References 54 publications
(84 reference statements)
1
20
0
Order By: Relevance
“…In addition, lineage 1 of WNV has been recently detected in blood donors of Pakistan (east of Iran) [31] and in mosquito pools, Aedes albopictus and Cx. pipiens s.l., in Turkey (northwest of Iran) [32]. Other similar investigations have also proved the circulation of WNV lineage 1 in Turkey, bordered with Iran [33][34][35].…”
Section: Introductionmentioning
confidence: 65%
See 2 more Smart Citations
“…In addition, lineage 1 of WNV has been recently detected in blood donors of Pakistan (east of Iran) [31] and in mosquito pools, Aedes albopictus and Cx. pipiens s.l., in Turkey (northwest of Iran) [32]. Other similar investigations have also proved the circulation of WNV lineage 1 in Turkey, bordered with Iran [33][34][35].…”
Section: Introductionmentioning
confidence: 65%
“…Vector competence assays should be combined with an active monitoring of WNV lineage 1 circulation in Iran [31,32]. We used a lineage 1 strain to assess vector competence of Cx.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The possible involvement of Ae. albopictus as a bridge vector in the WNV cycle was deduced due to WNV positive pools collected in the field in the U.S. (21) and Turkey (22), and the vectorial competence demonstrated in experimental studies (23,24). The possible vector role of Ae.…”
Section: Discussionmentioning
confidence: 99%
“…A recent study performed by Akiner and colleagues (2019) in Turkey, found WNV by PCR in Ae. albopictus collected in the field [52]. However, WNV has not as yet been isolated from Ae.…”
Section: Fecal-oral Transmissionmentioning
confidence: 99%